2020
DOI: 10.1073/pnas.1911382117
|View full text |Cite
|
Sign up to set email alerts
|

An integrative approach to the facile functional classification of dorsal root ganglion neuronal subclasses

Abstract: Somatosensory neurons have historically been classified by a variety of approaches, including structural, anatomical, and genetic markers; electrophysiological properties; pharmacological sensitivities; and more recently, transcriptional profile differentiation. These methodologies, used separately, have yielded inconsistent classification schemes. Here, we describe phenotypic differences in response to pharmacological agents as measured by changes in cytosolic calcium concentration for the rapid classificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(75 citation statements)
references
References 26 publications
3
65
0
Order By: Relevance
“…Further functional analyses showed that RIIIJ was indeed~100 more potent against hetero-tetramers made of three copies of Kv1.2 α-subunits and one of either Kv1.1 or Kv1.6 in a 3:1 stoichiometry [82]. This detailed functional and biochemical characterization then enabled the use of RIIIJ as a molecular tool for the classification of live large DRG neurons into six discrete functional populations [83]. An approach that can be exploited to accelerate the classification and study of other cell types within mixed population.…”
Section: Kv1-active Toxins In Research and Drug Discoverymentioning
confidence: 92%
See 1 more Smart Citation
“…Further functional analyses showed that RIIIJ was indeed~100 more potent against hetero-tetramers made of three copies of Kv1.2 α-subunits and one of either Kv1.1 or Kv1.6 in a 3:1 stoichiometry [82]. This detailed functional and biochemical characterization then enabled the use of RIIIJ as a molecular tool for the classification of live large DRG neurons into six discrete functional populations [83]. An approach that can be exploited to accelerate the classification and study of other cell types within mixed population.…”
Section: Kv1-active Toxins In Research and Drug Discoverymentioning
confidence: 92%
“…Recently, the discerning sensitivity of RIIIJ to its heteromeric Kv1 channel target was exploited to comprehensively classify and characterize individual somatosensory neuronal subclasses within heterogenous populations of dorsal root ganglion (DRG) neurons [83]. RIIIJ's selectivity was used to distinguish two functional Kv1 complexes in mouse dorsal root ganglion (DRG) neurons.…”
Section: Of 28mentioning
confidence: 99%
“…The peptide has also been characterized using calcium imaging combined with a pharmacological separation of different neuronal subtypes within the lumbar dorsal root ganglion of mice, a platform called Constellation Pharmacology [20]. The results of the constellation pharmacology analysis revealed that the peptide is surprisingly potent in mammalian systems, with nanomolar affinity for its targets.…”
Section: Discussionmentioning
confidence: 99%
“…This method was recently successfully employed to obtain conopeptide AtVIA (V28L:T30S) [15]. 20), and ribbon (Cys3-20, Cys9-15) forms of cdg14a were synthesized following a two-step oxidative folding: first in the presence of reduced and oxidized glutathione to form the first disulfide bridge, followed by folding in the presence of iodine to facilitate the second disulfide bond formation. Based on the co-elution experiments with the peptide obtained in a one-step, glutathione-assisted folding experiment (which co-eluted with the native peptide) and the product of a two-step directed folding ( Figure S5, Supplementary Information), it was established that the native peptide has the globular (Cys3-15, Cys9-20) fold, and the kinetically favored form, cdg14a_pk2, has the bead (Cys3-9, Cys15-20) fold ( Figure 5D).…”
Section: Chemical Synthesis Of Cdg14amentioning
confidence: 99%
“…Although DRG neurons are heterogeneous and highly specialized (Zheng et al, 2019;Giacobassi et al, 2020) the simple answer to the question of which neuronal types are affected by nerve injury is "probably all of them depending on the nature of the injury" (see Table 2).…”
Section: Which Types Of Sensory Neuron Are Affected?mentioning
confidence: 99%